Effects of sertraline on zebrafish (Danio rerio) - Moreira, Diana Raquel Gomes (2021)
The increasing consumption of antidepressants has resulted in its presence in the aquatic environment. This fact has aroused concerns in the scientific community since these biologically active compounds can affect non-target organisms that have physiological systems regulated by these pharmaceuticals. Sertraline (SER) is an antidepressant belonging to the serotonin reuptake inhibitors class (SSRI) and has a high consumption rate. However, there is little knowledge about the toxicological effects of SER in aquatic systems. Thereby, in the Chapter 2 of the present work, a review of the available literature, published in the last five years, addressing levels of antidepressants and its metabolites in rivers, surface waters, tap water, and wastewater treatment plants, as well, the effects reported in fish and invertebrates. Overall, the available laboratory studies show that antidepressants can disrupt multiple biological processes in aquatic organisms, having a detrimental effect. Thus, this study aims to evaluate the short-term (0.1 up to 3000 µg.L-1 ) and long-term (2 up to 1000×103 ng.L-1 ) effects of SER on zebrafish (Danio rerio) assessing different endpoints, such as development (e.g., mortality, spontaneous movements, equilibrium, abnormalities and heartbeat rate), biochemical markers associated with neurotransmission (acetylcholinesterase (AChE)), antioxidant defences (catalase (CAT), glutathione S-tranferases (GSTs)), energy metabolism (lactate dehydrogenase (LDH)) and behaviour (response to light/dark stimulus). Zebrafish embryos demonstrated sensitivity to SER concentrations during development (e.g., decreased spontaneous movements and increased/decreased heartbeat rate, depending on the exposed concentration). Regarding biochemical biomarkers assessed, in short-term exposure GSTs activity was significantly increased, and both in short- and long-term exposures the enzymatic activity of LDH was significantly increased. The responses to light/dark stimulus were generally decreased in short-term exposure, whereas the responses were increased in long-term exposure. These findings support further research on the long-term effects of antidepressants such as SER to aquatic biota and the development new methodologies to efficiently remove them from the environment.